Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2014
DOI: 10.1145/2556288.2557350
|View full text |Cite
|
Sign up to set email alerts
|

Design considerations for parallel performance tools

Abstract: In recent years there has been a shift in microprocessor manu facture from building single-core processors towards provid ing multiple cores on the same chip. This shift has meant that a much wider population of developers are faced with the task of developing parallel software: a difficult, time con suming and expensive process. With the aim of identifying issues, emerging practices and design opportunities for sup port, we present in this paper a qualitative study in which we interviewed a range of software … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In interviews carried out for a previous study [23], this was found to be a difficult issue. The model does not provide clear indications to reliably support identification of this problem as the expert assessments were in disagreement.…”
Section: Familiar and Frequent Problemsmentioning
confidence: 96%
See 4 more Smart Citations
“…In interviews carried out for a previous study [23], this was found to be a difficult issue. The model does not provide clear indications to reliably support identification of this problem as the expert assessments were in disagreement.…”
Section: Familiar and Frequent Problemsmentioning
confidence: 96%
“…Bug Classifications. It has been argued that within parallel program development, the distinction between performance problems and bugs is much less clear than in traditional software development [23]. However, the vast majority of parallel performance problems would receive only the broadest categorization under existing taxonomies.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations